2022
DOI: 10.3928/24748307-20220523-01
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Profiles of Early Intervention Providers: Use of the Health Literacy Questionnaire

Abstract: Background: Early intervention (EI) providers work with parents of children with or who have risk factors of developmental delay or disability through Part C of the Individuals with Disabilities Education Act. Many parents in the United States have low health literacy; therefore, EI providers should be aware of and address families' health literacy needs. EI providers need to be health literate themselves to implement evidence-based recommended practices. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“… 46 Coleman and colleagues demonstrated that healthcare professionals overestimate their understanding of HL limitations from patients, and with a proper, targeted intervention, these understandings may become more realistic. 47 , 48 Several studies have demonstrated the effectiveness in improving awareness of HL disparities in providers after training interventions as promoting knowledge, behaviors, and confidence in using HL strategies with patients and their families. 49 – 52 …”
Section: Discussionmentioning
confidence: 99%
“… 46 Coleman and colleagues demonstrated that healthcare professionals overestimate their understanding of HL limitations from patients, and with a proper, targeted intervention, these understandings may become more realistic. 47 , 48 Several studies have demonstrated the effectiveness in improving awareness of HL disparities in providers after training interventions as promoting knowledge, behaviors, and confidence in using HL strategies with patients and their families. 49 – 52 …”
Section: Discussionmentioning
confidence: 99%